A study on scar revision - Ashutosh Talwar; Neerja Puri (Our Dermatology Online, 2016)
Introduction: Scars are psychologically distressing for the patients and have an impact on the quality of life and self esteem of the patients. Scar revision is an aesthetic skill which is mastered by plastic surgeons and encroached now by dermatosurgeons. Scars on the face are aesthetically unacceptable and various techniques have been improvised for making a scar aesthetically acceptable. Various types of techniques are used for scar revision like W plasty, Z plasty and VY plasty. Aims: To see the efficacy of various scar revision techniques including Z plasty, VY plasty and W plasty in 30 patients with disfiguring scars. Methods: We selected twenty patients of disfiguring scars for the study. The scars from various causes including trauma and burns were included in our study. Various techniques of scar revision include Z plasty, W plasty and VY plasty were performed according to the type and site of scar. Results: Male: female was 1.5: 1. The scar revision surgery yielded excellent results with minimal complications including haematoma formation, secondary infection and delayed healing seen in 5% patients each. Regarding the efficacy of scar revision, excellent improvement was seen in 60% patients, moderate improvement was seen in 30% patients and mild improvement was seen in 10% patients. Conclusions: Dermatologists can employ a number of surgical scar revision techniques. While some are better suited to treat specific types of scars, they can be used in combination with each other or with adjunctive therapies to achieve optimal results.